Temperature as Thumb Rule Predictor of Ozone Levels in Santiago de Chile Ground Air - Lissi-Gervaso, E; Rubio-Campos, M (Sociedad Chilena de Quimica, 2014)
Ozone concentrations in the urban air of Santiago de Chile frequently surpass the air quality standard in summertime, particularly in the eastern part of the city (Las Condes). The main parameter that determines ozone episodes is the ground level daily maximum temperature. In the present work we propose that this single parameter can be employed as a simple predictor of the expected ozone levels. In particular, it is found that high ozone episodes takes place in Las Condes when the maximum daily temperature is higher than 30 °C. This single criterion applies during all the summer period (from December to March) and for weekdays and weekends. On the other hand, ozone episodes in downtown take place only when the maximum daily temperature reaches values higher than 32.5 °C. These simple relationships imply that weather forecast could be employed by the citizens to estimate the risk associated to carry out outdoors activities. © 2014, Sociedad Chilena de Quimica. All rights reserved.